W.G. McAdoo papers - McAdoo, W. G. (William Gibbs), 1863-1941.
Correspondence, memoranda, speeches, writings, reports, scrapbooks, bulletins, printed matter, photographs, and other papers relating chiefly to McAdoo's career as a lawyer and businessman in Tennessee and New York, U.S. secretary of the treasury and director general of railroads in the United States Railroad Administration during the Woodrow Wilson presidential administration, and U.S. senator from California. Also documents his role in Democratic Party politics in the 1920s. Correspondents include Woodrow Wilson and members of his Cabinet. Also includes correspondence of the Floyd, McAdoo, and Gibbs families.
Microfilm edition of containers 1-12 available
Microfilm produced from originals in the Manuscript Division.
Lawyer, business executive, U.S. secretary of the treasury, and U.S. senator from California.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Finding aid published by the Library of Congress, 1959.
Keywords: Wilson, Woodrow, -- 1856-1924 -- Correspondence; Floyd family -- Correspondence; Gibbs family -- Correspondence; McAdoo family -- Correspondence; United States. -- Congress. -- Senate; United States. -- Department of the Treasury. -- Office of the Secretary; Democratic Party (U.S.); United States Railroad Administration. -- Director General of Railroads; Business enterprises -- New York (State); Business enterprises -- Tennessee; Cabinet officers -- United States -- Correspondence; Practice of law -- New York (State); Practice of law -- Tennessee; Railroads -- United States; California -- Politics and government -- 1850-1950.; United States -- Economic policy -- 20th century; United States -- Politics and government -- 1901-1953.; Businessmen; Cabinet officers; Lawyers; Senators, U.S. Congress -- California